The image of the Prophet Muhammad in the context of understanding Islam in Japan in the first half of the 20th century - Oleksandra Bibik (Cхід, 2018)
The article is devoted to the analysis of the different variations of the image of the Prophet Muhammad and the elucidation of the features and understanding Islam in Japan in the first half of the 20th century. Islam is considered in the context of the religious, political and cultural environment. This religion makes attempts to synthesize Muslim teaching with Japanese religious traditions. On the other hand, Islam was applied for the development of pan-Asian ideology. The study of the perception of this religion in Japan will help understand the nature of the phenomenon that played a significant role in the development of the country at the turn of the century. As a result of the research have been established the features of the historical perception of Muhammad as a hero and the religious interpretation of the prophet as the founder and leader of Islam. Also, in this research have been found that the main feature of Islam is the tendency to syncretize various religious traditions - Shinto, Buddhism, and Confucianism with Muslim teaching. The article is showing how this understanding of Islam in Japan was formed and what factors influenced its development.